The reality which is to come Striving towards transcendence in times of Global Screen - García Lozano, Francisco José (Razón y fe, 2018)
This article offers the keys to understanding what spiritual cinema is and what it means. Although it resembles religious cinema, spiritual film differs in that it is capable, through its use of the third sense, of leading to spectators striving towards transcendence which displays, through stasis, an image of a second reality. It is also capable of representing the other fully. At the same time, it fills the human heart and brings the heart closer to new sources of meaning.